Carbon Footprint Optimization in The Palm Oil Industry - Wike Pratiwi; Zulhalifah Zulhalifah; Norma Juniati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
This optimization can be done through the application of carbon accounting methods, the use of renewable energy, efficient waste management, and low-emission technology innovation. This study aims to analyze the main sources of greenhouse gas (GHG) emissions and formulate a carbon footprint optimization model in the palm oil industry at PT X. The method used is a descriptive quantitative approach with optimization simulation based on methane capture on liquid waste (POME). The results show that POME is the largest emission contributor (45%), followed by fertilizer (30%), fuel (20%), and electricity (5%). The application of methane capture technology can reduce emissions from 16,400 tons of CO₂e/year to 3,280 tons of CO₂e/year or by 80%. Cost analysis shows a carbon cost of IDR 305,000 per ton of CO₂e and can be reduced to IDR 155,000 per ton of CO₂e with the presence of carbon credits. These results indicate that methane capture is an effective and efficient optimization strategy in reducing carbon emissions in the palm oil industry. In conclusion, the largest source of carbon emissions at PT X comes from POME liquid waste, making it a top priority in the mitigation strategy. The implementation of methane capture has proven effective in reducing emissions by 80%, or 13,120 tons of CO₂e per year.